Perlindungan Hukum Bagi Kreditur Apabila Akta Jaminan Fidusia Tidak Didaftarkan Oleh Notaris - Nagita Pujiastuti Djafar; Nirwan Junus; Mohamad Taufiq Zulfikar Sarson (International Forum of Researchers and Lecturers, 2024)
This research aims to determine the legal protection for creditors if the fiduciary guarantee deed is not registered by a notary, and the legal implications if the fiduciary guarantee is not registered by a notary. The method used in this research uses the Juridical Sociology method.The results of the research show that a fiduciary agreement which makes the object of collateral (in the form of objects) in a subsidiary agreement (acessoir) of the main agreement has weak legal protection for creditors if the agreement is not registered by a Notary through the Fiduciary Guarantee Institute, as stipulated in the Law Number 42 of 1999 concerning Fiduciary Guarantees. The legal implications for creditors' rights because they do not comply with the principle of publicity as per the applicable consensus, in this case is Law Number 42 of 1999 concerning Fiduciary Guarantees which regulates Preferential Rights and Executorial Rights.For the implementation of financing by making objects into objects, an agreement process should be carried out in accordance with the Fiduciary Guarantee consensus by referring to Law Number 42 of 1999, by fulfilling the principle of publicity as the main legal principle in material guarantee law.